Simulating the detection and classification of high-redshift supernovae with HARMONI on the ELT. Issue 3 (15th February 2018) - Bounissou, S; Thatte, N; Zieleniewski, S; Houghton, R C W; Tecza, M; Hook, I; Neichel, B; Fusco, T
Abstract: We present detailed simulations of integral field spectroscopic observations of a supernova in a host galaxy at z  ∼ 3, as observed by the HARMONI spectrograph on the Extremely Large Telescope, assisted by laser tomographic adaptive optics. The goal of the simulations, using the HSIM simulation tool, is to determine whether HARMONI can discern the supernova type from spectral features in the supernova spectrum. We find that in a 3 h observation, covering the near-infrared H and K bands, at a spectral resolving power of ∼3000, and using the 20 × 20 mas spaxel scale, we can classify Type Ia supernovae and their redshift robustly up to 80 d past maximum light (20 d in the supernova rest frame). We show that HARMONI will provide spectra at z  ∼ 3, which are of comparable (or better) quality to the best spectra we can currently obtain at z  ∼ 1, thus allowing studies of cosmic expansion rates to be pushed to substantially higher redshifts.